THE EFFECT OF NON-PHARMACOLOGICAL INTERVENTION ON VITAL SIGNS IN PREGNANT WOMEN WITH HYPERTENSION - Pratiwi, Rizqi Dian (Indonesian Midwifery and Health Sciences Journal, 2025)
Abstract Background: Pregnancy induced Hypertension (PIH) is a significant cause of maternal and fetal death. Although, the intervention approach that takes into account physical and psychological conditions is not yet optimal. This study aims to determine the efforts of relaxation technique therapy on the difference in heart rate dan oxygen saturation level (SpO2) in pregnant women with hypertension. Method: This study used a cross-over design. A total of 36 pregnant women with third trimester hypertension obtained by random sampling technique were given bed rest therapy for 5 days 1 x 20 minutes and given relaxation therapy for 5 days 1 x 20 minutes. Bedrest is a health treatment where the client lies in bed certain period of time and relaxation therapy is techniques involve tensing and relaxing muscles in sequence which is a psychological mechanism that connects the mind and body. Measurements using a pulse oximeter. Data were analyzed using the Friedman and Wilcoxon tests. Results: The results of the study showed a significant difference in relaxation technique therapy and bed rest therapy on reducing in normal heart rate (P <0.001) and oxygen saturation levels (SpO2) with P < 0,05. The average decrease in heart rate and increased oxygen saturation levels (SpO2) was greater in the relaxation technique therapy group and the confounding variables have no effect on either. Conclusion: Relaxation techniques can reduce heart rate and increased SpO2 to optimal in pregnant women with hypertension. Relaxation techniques can be a complementary therapy in midwifery care for pregnant women with hypertension.